Singapore : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This Selected Issues paper examines the behavior of savings and investment from an Asian and Singaporean perspective. It builds and estimates two econometric models that relate savings and investment to a range of macroeconomic and structural variables. The paper examines the relationship between labor market developments and private consumption behavior, and notes that employment uncertainty did have a significant negative impact on consumption and raised precautionary savings. It also examines quantitative, industry-level measures of the intensity of domestic competition in the manufacturing and services sectors during the past two decades in Singapore.